Psychometric properties of the Barthel Index for evaluating physical function among Chinese oldest‐old. Issue 2 (22nd February 2022) - Zhang, Chi; Zhang, Xuxi; Zhang, Hao; Zeng, Ping; Yin, Pengbin; Li, Zhongquan; Zhao, Yali; Yao, Yao
Abstract: Background: The Barthel Index (BI) is among the most widely used instruments for evaluating physical function, yet its applicability has not been well studied in the oldest‐old population. Objective: To test the psychometric properties of the BI for evaluating physical activities of daily living (ADL) in a large representative sample of oldest‐old population in China. Methods: Participants were 1750 oldest‐old adults (aged 80–116 years, 72.11% female) including 956 centenarians. ADL were assessed during face‐to‐face interviews. Multiple methodologies were applied to evaluate the reliability, validity and measurement invariance of the BI. An item response theory (IRT) framework was conducted to estimate the parameters of each item. Results: 48.91% participants had function dependence. Cronbach's α coefficient of the BI was 0.902, but 'Stair climbing' impaired the overall internal consistency. The known‐group validity of the BI was confirmed by significant differences in the BI score across age ( P  < 0.001), gender ( P  < 0.001), education ( P  < 0.001) and ethnicity ( P  = 0.038). The criterion‐related validity was supported by significant correlations between the BI score with depression symptoms ( r  = −0.36, P  < 0.001), subjective well‐being ( r  = 0.23, P  < 0.001) and self‐report health status ( r  = 0.22, P  < 0.001). Factor analysis yielded a two‐factor structure (somatic function and physiological self‐care) with appropriate invariance. Ten items showed acceptable discrimination parameters (1.80–5.87) and difficulty parameters (−2.65–1.11) but had variant test information (1.73–10.22). 'Bower control' and 'Bladder control' were not conducive to the local independence. Conclusions: The BI has appropriate reliability, validity and measurement precision for community‐based Chinese oldest‐old and centenarians, but individual items have low quality. Somatic disability and incontinence are two latent categories of functional dependence in this population. Living environment needs to be taken into consideration for ADL instrument development and modification.